Penerapan Konsep Nilai Waktu Uang Pada Penyusutan Aktiva Tetap dan Pengaruhnya Terhadap Kewajiban Pajak pada PT Synergy Indonesia - Arniati Arniati; Fitrima Windariyani (JURNAL AKUNTANSI, EKONOMI dan MANAJEMEN BISNIS, 2013)
Tax planning is an attempt to minimize the taxation of corporate profits, can be done by selecting the appropriate method of depreciation. This study was conducted to determine the ratio of fixed assets depreciation calculations PT Synergy Indonesia if using straight-line depreciation method or the declining balance method taking into account the time value of money now (present value), and its influence on the acquired company's tax savings. This study will reveal the method of depreciation tax savings by PT Synergy Indonesia. The author uses interviews and documentation methods in order to obtain information / data accurately from the company. Results of this study suggest the company using the declining balance method as a method of depreciation of fixed assets of the company, because in this method the tax savings.